(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2018)
Background : Now a day’s bacterial vaginosis is an extremely common health problem for women in the world which causes many complications both in the pregnancy and non-pregnancy states. G. vaginalis is most important cause of bacterial vaginosis. Materials and methods : A cross sectional study was conducted to assess the role of Gardnerella vaginalis as an etiological agent of bacterial vaginosis. This study was undertaken to assess the patients attending at the outpatient department of Gynaecology and Obstetrics of Chittagong Medical College Hospital, Chittagong. A total of 170 sexually active female in the age group of 15-45 years, with abnormal vaginal discharge were selected for the study. A detailed history and a thorough clinical examination of all the cases were done. pH of the vaginal discharge was measured and three high vaginal swabs were collected. Bacterial vaginosis was diagnosed using Amsel’s criteria and Nugent’s method. Gardnerella vaginalis was isolated and identified with their drug sensitivity test by standard methods. Results : In this study 38(22.35%) Gardnerella vaginalis were isolated by culture and bacterial vaginosis was detected by Amsel clinical criteria (Clinical method) 43(25.30%), Gram stain Nugent criteria (Gold Standard) 45(26.47%).Our study showed a relatively high prevalence of bacterial vaginosis and high isolation rate of Gardnerella vaginalis within the positive bacterial vaginosis patients. Conclusion : This result helps proper management and treatment. JCMCTA 2017 ; 28 (2) : 81-87